2018
DOI: 10.1111/jfbc.12723
|View full text |Cite
|
Sign up to set email alerts
|

Neem, pawpaw and bamboo leaf meal dietary supplementation in broiler chickens: Effect on performance and health status

Abstract: The effect of the diet supplemented with leaf meals (LM) of neem (NLM), pawpaw (PLM), bamboo (BLM) and their composite leaf mix (CLM) on broiler chickens was assessed. Three hundred 1‐day old broiler chickens were distributed to five diets: (control/no LM), (5 g/kg NLM), (5 g/kg PLM), (5 g/kg BLM) and (5 g/kg NLM+PLM+BLM 1:1:1). Body weight gain of birds fed BLM and CLM supplemented diets were similar but higher (p < 0.05) than those fed the control, NLM and PLM supplemented diets at day 42. The glucose, trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 30 publications
5
44
2
Order By: Relevance
“…The Moringa seed offers concentrated nutrients including amino acids, proteins, and a wide range of vitamins and minerals, making it an outstanding supplement for stressed and hurried individuals and a solid source of nutrition for undernourished populations around the World (Peter & Philip, 2014). Furthermore, the fonio-moringa seed meal (FMSM) could be classified as phytogens (Abd El-Hack et al, 2018) and generally, phytogenic feed supplements or additives are reported to have influence on the heamatological and serum biochemical indices (Oloruntola, Agbede, Ayodele, & Oloruntola, 2018) and histology and morphology of internal organs of the animals (Adeyeye, Ayodele, Oloruntola, & Agbede, 2019;Oloruntola, 2018).…”
mentioning
confidence: 99%
“…The Moringa seed offers concentrated nutrients including amino acids, proteins, and a wide range of vitamins and minerals, making it an outstanding supplement for stressed and hurried individuals and a solid source of nutrition for undernourished populations around the World (Peter & Philip, 2014). Furthermore, the fonio-moringa seed meal (FMSM) could be classified as phytogens (Abd El-Hack et al, 2018) and generally, phytogenic feed supplements or additives are reported to have influence on the heamatological and serum biochemical indices (Oloruntola, Agbede, Ayodele, & Oloruntola, 2018) and histology and morphology of internal organs of the animals (Adeyeye, Ayodele, Oloruntola, & Agbede, 2019;Oloruntola, 2018).…”
mentioning
confidence: 99%
“…Erythrogram is one of the indicators for assessing the nutritional and health status of animals, and there exists a marked influence of nutrition on haematology traits (Oloruntola et al 2018d). The stability of packed cell volume, haemoglobin concentration and red blood cells of the birds fed diets containing varying levels of PCHM also shows that the dietary treatment used in this study did not have negative effects on the normal blood-forming processes in the experimental birds.…”
Section: Discussionmentioning
confidence: 57%
“…For instance, caffeine intake was associated with a lower risk of elevated alanine aminotranaferase (Ruhl and Everhart 2005). The use of phytochemical in ameliorating the negative effects of heat-induced oxidative stress in birds has been reported (Oloruntola et al 2018d). These phytochemicals with antioxidant properties play roles in reducing the process of oxidation by reacting with free radicals during oxidative process (Goyal and Brahma, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations